(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Sustainable financing is being practiced by financial institutions all over the world for creating economic and social values adopting policies, systems, and models to reduce the environmental and social cost incurred in the course of business. In many countries, financial institutions adopt pro-environment and sustainable financial models, design innovative eco-friendly products and create markets to make this world more sustainable. The study revealed a positive response in implementing the sustainability issues by the banks in various capacities under the guidance of the Central Bank. The outcome of the paper is expected unveil the position of the bank practitioners and policy makers about the sustainability concepts and current status sustainability initiatives taken by the regulatory authority in the banking industry.